Fractional Subequation Method for Cahn-Hilliard and Klein-Gordon Equations - Hossein Jafari; Haleh Tajadodi; Nematollah Kadkhoda; Dumitru Baleanu (Abstract and Applied Analysis)
The fractional subequation method is applied to solve Cahn-Hilliard and Klein-Gordon equations of fractional order. The accuracy and efficiency of the scheme are discussed for these illustrative examples.